Mid-century modern complete - Bradbury, Dominic (Thames & Hudson, 2014)
This definitive survey of one of the most popular collectible and dynamic periods of international design offers a rich overview of all aspects of the subject. Mid-century furniture, lighting, glass, ceramics, textiles, product design, industrial design, graphics, and posters are covered, as are interior design and architecture, exemplifying post-war optimism and energy, use of innovative and affordable materials and forms of mass manufacture, and newly developed precepts of "good design."